Towards Open-Source Web-Based 3D Reconstruction for Non-Professionals - Dietz, Oliver; Grubert, Jens (Frontiers in Virtual Reality, 2022)
Structure-from-motion and multi-view stereo can be used to create 3D models from image sequences, but are not widely adopted by consumers. We study how to address two challenges of such systems for non-professional users: 1) their technical complexity, and, 2) the computational demand needed for processing. To this end, we embed an open-source pipeline in a scalable cloud environment and create a user interface aimed at non-professional users of photogrammetry systems. Finally, we evaluate both the cloud-based infrastructure and the user interface and demonstrate its usability.